1967
DOI: 10.1111/j.1432-1033.1967.tb19514.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Salts on RNA Synthesis by DNA‐Dependent RNA‐Polymerase from Escherichia coli

Abstract: The effect of salt concentration on RNA synthesis by DNA-dependent RNA-polymerase from Escherichia coli has been investigated. For a double stranded template the following influences are observed: (1) Free enzyme and enzyme bound to DNA, but not synthesizing RNA, are inhibited above an ionic strength of about 0.15. (2) The rate of RNA-synthesis, by those enzyme molecules which have started RNA chains, is stimulated by increasing the salt concentration up to an optimum. Magnesium salts cause a larger stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

1968
1968
1977
1977

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(78 citation statements)
references
References 45 publications
7
71
0
Order By: Relevance
“…This finding is in disagreement with that of Spelsberg and Hnilica [13] who found that as much as 2Z0/, of histone f l was released from chromatin by 0.20 M Thus we would predict that the RNA-polymerase molecules which are bound to the chromatin and are actively involved in RNA synthesis at the time of the isolation of the chromatin are unable to continue transcription until protein which is blocking further movement of the polymerase along the DNA is released from the template. At high salt concentration therefore, the RNA-polymerase activity is probably only due to the elongation of previously initiated RNA chains as the elongation process is not (in bacterial systems anyway) sensitive to high ionic strength [51]. This process will be discussed further below.…”
Section: Chromatin Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in disagreement with that of Spelsberg and Hnilica [13] who found that as much as 2Z0/, of histone f l was released from chromatin by 0.20 M Thus we would predict that the RNA-polymerase molecules which are bound to the chromatin and are actively involved in RNA synthesis at the time of the isolation of the chromatin are unable to continue transcription until protein which is blocking further movement of the polymerase along the DNA is released from the template. At high salt concentration therefore, the RNA-polymerase activity is probably only due to the elongation of previously initiated RNA chains as the elongation process is not (in bacterial systems anyway) sensitive to high ionic strength [51]. This process will be discussed further below.…”
Section: Chromatin Transcriptionmentioning
confidence: 99%
“…by Rifampicin APIO-13 Three steps in RNA synthesis in vitro can be distinguished each of which have certain ionic strength requirements : (a) the binding of the enzyme to the DNA and the stabilisation of the complex by the first nucleotide in the RNA chain (initiation) which can take place up to an ionic strength of about 0.4 [51,52]; (b) elongation of the RNA chain which appears to be independent of the ionic strength up to quite high levels [51]; (c) release and reinitiation of new RNA chains which only occurs a t an ionic strength of about 0.2 (see review [24]). This data has all been derived from the study of the DNA-dependent RNA polymerase of Escherichia coli.…”
Section: Inhibition Of Rna Synthesismentioning
confidence: 99%
“…This RNA, which is transcribed from a point near the origin of X replication (20,21), provides an attractive system for several reasons. First, the nucleotide sequence of the 4S RNA as well as the sequence of Xpga18 for approximately 35 nucleotides beyond the 3' end of the transcript have been determined (22). Second, the similarities between 4S RNA and an RNA "leader" sequence in the tryptophan operon suggest that in vivo the 4S may serve as a leader and its termination site as an attenuator (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…The size of RNA synthesized in vitro under these conditions with T3, T7 or T4 DNA as template is of 3000 to 7000 nucleotides length [8,9]. Only at relatively high ionic strength under these pH conditions is the enzyme able to reinitiate [10]. However at low pH (5.7-6.0) and low ionic strength (3-12 mM Mg 2+ and 10-40 mM KC1), the rate of RNA synthesis was much lower, but did not reach a plateau and continued for several hours with a rate of synthesis much lower than at optimal conditions ( fig.la).…”
Section: Resultsmentioning
confidence: 99%